Pengaruh KH. Hasyim Asy’ari dalam Membangun Serta Menjaga Nusantara dan Kemaslahatan Islam Dunia - Fakturmen Fakturmen; Muhammad Zaenul Arif (JURNAL INDO-ISLAMIKA, 2020)
This article discusses about the influence of KH. Hasyim Asy'ari regarding his efforts in building and maintaining the integrity of the nation, both in the Islamic and national fields and his role in resolving the Islamic context at the International level (Hijaz). The research method used is literature study by means of descriptive content analysis. The results of this study indicate that KH. Hasyim Asy'ari is a figure who has a great influence in regulating national and Islamic stability both in thought (aqliyah) and movement (amaliyah) so that it stands the Unitary State of the Republic of Indonesia. Besides that, the important role of KH. Hasyim Asy'ari is both as an advisor and a legitimator in an effort to preserve the purity of Islam at the international level, namely the polemic of the sovereigns in the Hijaz land. The influence in the archipelago includes: the da'wah ukhuwah Islamiyah as a form of tolerance, the value of leadership towards the people and nation, intellectual contributions as Muslim scholars, influence and commitment against the invaders while his influence at the international level is to maintain the purity and benefit of the world Islam (Hijaz).